Hyperspectral imaging to classify and monitor quality of agricultural materials. (March 2015) - Mahesh, S.; Jayas, D.S.; Paliwal, J.; White, N.D.G.
Abstract: Hyperspectral imaging has been acknowledged as an emerging technology for monitoring quality parameters and improving grading of agricultural materials, such as field crops (e.g., cereals, pulses, oil seeds) and horticultural crops (e.g., apples, strawberries). It has become a popular research tool that facilitates thorough non-destructive analyses by simultaneous acquisition of both spectral and spatial information of agricultural samples. The technique is an extension of multispectral imaging, which provides a large data set by applying conventional imaging, radiometry, and spectroscopic principles when acquiring images. Hyperspectral imaging was initially used for remote sensing applications, but now has been developed to facilitate complete and reliable analyses of intrinsic properties and external characteristics of samples. This paper reviews applications of using hyperspectral imaging for routine grain industry operations such as grading, classification, and chemometric analyses of major constituents of agricultural materials. Highlights: The necessity for non-destructive quality analysis tool is emphasized. Major components of hyperspectral imaging systems (HSI) are reviewed. The HSI applications for assessing agricultural and horticultural materials are highlighted. Limitations of using HSI system are discussed.